Augmented Reality English to Malay words converter - Nur Shafiqah Syuhada, Abdul Basik (2018)
Augmented reality is like display something from a computer to a reality that will make the user feel like it is a true object being in front of the eyes. This project is about AR English to Malay Words Converter. English words will be markers in this project, while the Malay language will be displayed as AR. It will track every single word and will be checked in the database to retrieve Malay language data and display it through AR. Only detected words will be produced using AR. It is also very worthwhile for anyone, especially to anyone who wants to reduce the bag weight, to speed up time and avoid forgetting if it is located in another place. From the existing application, it can help to lessen what is not supposed to be in the system and what it should have in the system. From the applications that are assessed, there are bookmarks function, word history, online manual searches and the scanned words are sometimes incorrect and weird. Also, AR English to Malay words converter is still not in the market, so this is the opportunity to continue making this project. For this system, the purpose is to facilitate the user to scan the word and the user directly gets the meaning of the word correctly and logically. The function just simply scans the word. This system will be created using the Android platform because the percentage of Android users is more. There are many categories of basic words that people usually use in their daily life; the categories that are implement in this project are greetings, people, appearance, human body, mountains, countryside, coast, city, house, homes, transport, occupations, birthday, university campus, time, numbers, hobbies, buying things, learning, directions, travelling, clothes, colours, food and drinks, fruit, vegetables, herbs and spices, cooking, animals, weather, types of sick and festivals. By selecting the Waterfall methodology, I followed the step successfully without any repetition. By collecting data first before starting another process, it helps me to complete this project. Waterfall methodology is best suited for projects that are not too complicated, for example, this project. In fact, it also helps me to complete a phase in detail. In general, everything goes smoothly, though there are some weaknesses that cannot be avoided or discarded. The weaknesses and future work will also be improved and discussed.